Personally perceived publication pressure: revising the Publication Pressure Questionnaire (PPQ) by using work stress models - Tamarinde L. Haven; Marije Esther Evalien de Goede; Joeri K. Tijdink; Frans Jeroen Oort (Research Integrity and Peer Review, 2019)
Abstract Background The emphasis on impact factors and the quantity of publications intensifies competition between researchers. This competition was traditionally considered an incentive to produce high-quality work, but there are unwanted side-effects of this competition like publication pressure. To measure the effect of publication pressure on researchers, the Publication Pressure Questionnaire (PPQ) was developed. Upon using the PPQ, some issues came to light that motivated a revision. Method We constructed two new subscales based on work stress models using the facet method. We administered the revised PPQ (PPQr) to a convenience sample together with the Maslach Burnout Inventory (MBI) and the Work Design Questionnaire (WDQ). To assess which items best measured publication pressure, we carried out a principal component analysis (PCA). Reliability was sufficient when Cronbach’s alpha > 0.7. Finally, we administered the PPQr in a larger, independent sample of researchers to check the reliability of the revised version. Results Three components were identified as ‘stress’, ‘attitude’, and ‘resources’. We selected 3 × 6 = 18 items with high loadings in the three-component solution. Based on the convenience sample, Cronbach’s alphas were 0.83 for stress, 0.80 for attitude, and 0.76 for resources. We checked the validity of the PPQr by inspecting the correlations with the MBI and the WDQ. Stress correlated 0.62 with MBI’s emotional exhaustion. Resources correlated 0.50 with relevant WDQ subscales. To assess the internal structure of the PPQr in the independent reliability sample, we conducted the principal component analysis. The three-component solution explains 50% of the variance. Cronbach’s alphas were 0.80, 0.78, and 0.75 for stress, attitude, and resources, respectively. Conclusion We conclude that the PPQr is a valid and reliable instrument to measure publication pressure in academic researchers from all disciplinary fields. The PPQr strongly relates to burnout and could also be beneficial for policy makers and research institutions to assess the degree of publication pressure in their institute.